Penerapan algoritma sequential search pada sistem pencarian data naskah dinas - Diana, Nirma Nur (Maliki Interdisciplinary Journal, 2024)
The current method for data retrieval from the governor’s official documents is cumbersome and inefficient. Manual note-taking in a bulky ledger and retracing previous letters to assign numbers proves impractical, especially for long-term archiving of numerous document types. Additionally, the conventional search process is time-consuming. This research introduces a sequential search algorithm to streamline data retrieval from the governor’s documents. This algorithm systematically examines each data point until the target is found. The system is designed for the Head of Administrative and Administrative Affairs (Kaurmintu), responsible for managing letter classifications, employee positions, incoming/outgoing letters, and issuing directives for action by employees. Employees themselves only access directives originating from Kaurmintu. The implemented system, utilizing the sequential search algorithm, has demonstrably simplified and accelerated data retrieval within the governor’s official documents.